2008
DOI: 10.1007/s11095-008-9562-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Particle Size in Phagocytosis of Polymeric Microspheres

Abstract: Purpose-Polymeric microspheres are extensively researched for applications in drug and vaccine delivery. However, upon administration into the body, microspheres are primarily cleared via phagocytosis by macrophages. Although numerous studies have reported on the biochemical pathways of phagocytosis, relatively little is known about the dependence of phagocytosis on particle size. Here, we investigate the previously unexplained dependence of phagocytosis on particle size.Methods-Rat alveolar macrophages and Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
595
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 762 publications
(627 citation statements)
references
References 35 publications
(37 reference statements)
27
595
2
3
Order By: Relevance
“…The phagocytic ability of mammalian macrophages is impaired for larger phagocytic targets [27]. Here we demonstrate that the same phenomenon occurs in D. melanogaster.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The phagocytic ability of mammalian macrophages is impaired for larger phagocytic targets [27]. Here we demonstrate that the same phenomenon occurs in D. melanogaster.…”
Section: Discussionsupporting
confidence: 65%
“…We test whether the number of circulating haemocytes declines with age and also whether the haemocytes of older individuals have impaired phagocytic activity. Vertebrate macrophages are less efficient at phagocytosing larger particles [27]. With the expectation that the same would be true for D. melanogaster haemocytes, we investigate whether the rate at which phagocytosis ability senesces is faster for larger, more challenging targets.…”
Section: Introductionmentioning
confidence: 98%
“…The potent TLR agonist polyIC was formulated in biodegradable MPs or NPs using the Food and Drug Administrationapproved polymer poly(lactide-co-glycolide). Consistent with earlier studies suggesting that phagocytosis by macrophages and DCs is efficient for submicron-sized particles but much less effective for particles >3.0 μm in diameter (29,30), we found that the fate of particles injected i.LN could be controlled by the simple physical parameter of particle size: NPs were taken up to high levels by LN-resident APCs, whereas MPs remained largely extracellular over several days (Fig. 1 D-F).…”
Section: Discussionsupporting
confidence: 91%
“…Beyond RBCs, cancer cells, especially metastatic cancer cells, are elastically softer than healthy cells, a characteristic that is believed to be integral to their ability to spread to new locations (1,4). Although much attention has been directed toward the enhancement of the circulation time of particles, including alterations of particle size (5,6), shape (7)(8)(9), and surface characteristics (10), the role played by deformability in the in vivo circulation profile of particles has not been well explored.…”
mentioning
confidence: 99%